(untitled) (Jurnal Bina Praja, 2025)
Land border management between the Republic of Indonesia (RI) and the Democratic Republic of Timor-Leste (RDTL) is hindered by structural fragmentation, resulting in a dichotomy between security and welfare approaches. Although policy has shifted from a hard border approach to a soft border, its implementation is still dominated by the sectoral egos of security and development institutions. This situation results in grandiose infrastructure development, often masking underlying problems such as poverty and low institutional capacity. This study uses a qualitative approach with policy document analysis and semi-structured interviews in Belu Regency. This article aims to criticize the weaknesses of the existing dual governance model and propose a more effective integrated solution. Using the theoretical framework of the Penta-Helix Model, this study analyzes the roles of the Government, Academics, Business Actors, Communities, and the Media. The results show that the participation of non-state actors remains peripheral and uninstitutionalized. As a key contribution, this article proposes an Integrated Border Governance Model (IBGM). This model rejects the concept of dual Centers of Gravity and instead proposes the establishment of a co-chaired Governance Council for consensus-based decision-making. The IBGM model offers a path to achieving national security through a synergy between sovereignty and welfare, transforming the border from a dividing line to a bridge of shared prosperity and security.